Controllable-release solid corrosion and scale inhibitor and preparation method thereof

By combining modified hydrotalcite-like materials with scale-proofing and corrosion-proofing active components, a controlled-release solid corrosion-proofing agent is prepared, which solves the problem of inability to regulate the release rate and unstable effect in the prior art, and achieves efficient and stable scale-proofing effect and environmentally friendly use.

CN119841469AActive Publication Date: 2025-04-18XIAN WATER INNOVATION MATERIALS TECH CO LTD

Patent Information

Application Number
CN202510326139.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

The existing corrosion inhibitors have problems with inaccurate release rate and unstable effects, which leads to low efficiency in different water treatment environments, and large-scale use will lead to excessive dissolution, affecting the safety of the water environment.

Method used

By modifying manganese nitrate, zinc nitrate, aluminum nitrate and xanthan gum in a hydrothermal reaction, Mn-Zn-Al ternary modified hydrotalcite material was prepared, and mixed with scale-retardant active components to granulate to controllable release solid corrosion-retardant inhibitors of different particle sizes were prepared.

Benefits of technology

The controlled release of scale-resistance and corrosion-inhibiting active components is achieved, which improves the stability and durability of scale-resistance effect, reduces scale formation and metal corrosion, and reduces the dosage and environmental pollution risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841469A_ABST
    Figure CN119841469A_ABST
Patent Text Reader

Abstract

The invention relates to a controlled-release solid corrosion and scale inhibitor and a preparation method thereof, and belongs to the technical field of scale inhibition materials for water treatment. According to the preparation method of the controllably released solid corrosion and scale inhibitor, three metal salts (manganese nitrate, zinc nitrate and aluminum nitrate) are used as precursors, xanthan gum is used as a modifier, and a Mn-Zn-Al ternary modified hydrotalcite-like material is prepared through a hydrothermal reaction; further mixing, granulating and sieving the ternary modified hydrotalcite-like material and the scale and corrosion inhibition active component to prepare solid corrosion and scale inhibitors with different sizes. The solid corrosion and scale inhibitor provided by the invention can reduce the formation of scale and effectively delay the corrosion of metal, has a lasting action period, can realize the controlled release effect of the scale and corrosion inhibition active components, is beneficial to improving the utilization rate of water resources and reducing the use amount of water treatment aids, and has the advantages of environmental protection, environmental protection and the like. Meanwhile, the scale inhibitor has a good application prospect and development potential in development and application of the scale inhibitor for water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a controllably released solid corrosion and scale inhibitor and a preparation method thereof, belonging to the technical field of scale inhibitor materials for water treatment. Background Art

[0002] With the rapid development of modern industry, corrosion and scale inhibitors have been widely used in various water treatment environments such as domestic water and industrial circulating cooling water. Corrosion and scale inhibitors have the dual functions of corrosion inhibition and scale inhibition. On the one hand, they prevent oxidation and corrosion by forming a protective film on the metal surface. On the other hand, they can reduce the deposition of scale and reduce the wear and blockage of pipes and equipment. Therefore, the use of corrosion and scale inhibitors can not only reduce the losses caused by scaling and corrosion of water-using equipment and pipes, but also has important significance for extending the service life of equipment, improving water utilization and heat exchange efficiency.

[0003] At present, most of the common corrosion and scale inhibitor products inevitably involve the use of phosphorus-containing scale inhibitors (such as sodium ethylenediaminetetramethylenephosphonate, aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, polyol phosphate, 2-hydroxyphosphonoacetic acid, polyaminopolyether methylenephosphonic acid, etc.). Although they can achieve good scale inhibition effects, they are not easy to biodegrade, and long-term use will cause pollution and harm to the natural environment. Therefore, the development of corrosion and scale inhibitors with good biosafety is an important way to improve water quality and reduce environmental pollution.

[0004] In addition, with the rapid development of the economy and society, the application scenarios of scale inhibition and corrosion inhibition have gradually diversified, and the research and development focus of scale inhibitors has gradually shifted towards refinement and control. Faced with application scenarios with different water qualities (such as tap water, groundwater, etc.) and different pipe materials (such as carbon steel, copper pipes, etc.), the release requirements and application efficiency of scale inhibitors are different. Therefore, it is necessary to design the scale inhibition and corrosion inhibition components to be controllable according to actual needs, so as to achieve the purpose of high efficiency, controllability and improved material utilization. The controlled release strategy refers to the release process of scale inhibitors in different environments. By controlling the different dissolution rates and release rates of scale inhibitors in different environments, the effect of scale inhibitors can be specifically regulated and the dosage can be reduced. However, most of the existing corrosion and scale inhibitors have the problem that the release rate cannot be accurately regulated, the effect is unstable and long-lasting, and they are prone to failure. In actual application, for water treatment environments with serious scaling and corrosion, it is often necessary to increase the dosage and frequency of scale and corrosion inhibitors. However, the large-scale and repeated use of scale inhibitors not only increases the complexity of the operation, but also causes the dissolution to exceed the standard and reduces the safety of the water environment. This greatly limits the further application of scale and corrosion inhibitors in different water treatment environments, and is not conducive to improving the utilization efficiency of scale inhibitors.

[0005] Therefore, there is an urgent need to develop a green and environmentally friendly corrosion and scale inhibitor with controlled release function and stabilizing effect to meet the requirements of refined and controllable applications. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a solid corrosion inhibitor and scale inhibitor with controllable release, which has a simple process, mild conditions, and high biological safety of the prepared solid corrosion inhibitor and scale inhibitor. It can timely regulate the release rate of the corrosion inhibitor and scale inhibitor components according to the application scenario, thereby solving the problem that the release rate of the corrosion inhibitor and scale inhibitor cannot be accurately regulated and the effect is unstable.

[0007] At the same time, the purpose of the present invention is also to provide a controlled-release solid corrosion and scale inhibitor that can reduce the formation of scale and effectively delay metal corrosion, and has a long-lasting action period, and in particular can achieve the effect of controlled release of scale and corrosion inhibitor active components.

[0008] To achieve the above object, the first aspect of the present invention provides a method for preparing a controllable-release solid corrosion and scale inhibitor, comprising the following steps: (1) Mixing manganese nitrate, zinc nitrate, aluminum nitrate and xanthan gum in water, and then adjusting the pH of the system to 8-10 to obtain a mixed solution; transferring the mixed solution to a high-pressure reactor, and performing a hydrothermal reaction at a temperature of 110-130° C.; filtering the product after the reaction, and then washing, drying and grinding to obtain a modified hydrotalcite-like powder; (2) Dispersing the modified hydrotalcite-like powder in water to obtain a hydrotalcite-like dispersion; mixing the scale and corrosion inhibitor active component with a binder to obtain an active component mixed solution; adding the hydrotalcite-like dispersion to the active component mixed solution, mixing, and then granulating, drying, and sieving to obtain a solid corrosion and scale inhibitor with different particle sizes and controllable release.

[0009] In a preferred embodiment, in step (1), the manganese nitrate is manganese nitrate tetrahydrate; the zinc nitrate is zinc nitrate hexahydrate; and the aluminum nitrate is aluminum nitrate nonahydrate.

[0010] In a preferred embodiment, in step (1), the molar ratio of manganese nitrate, zinc nitrate and aluminum nitrate is 1: (0.8-1.2): (0.8-1.2), more preferably 1: 1: 1. The amount ratio of manganese nitrate, xanthan gum and water is 0.01 mol: (2-4) g: (50-80) mL, more preferably 0.01 mol: 3 g: 60 mL.

[0011] In a preferred embodiment, in step (1), the pH of the system is adjusted by using ammonia water or sodium hydroxide solution. Further preferably, the mass concentration of the ammonia water is 25% to 28%, and the concentration of the sodium hydroxide solution is 0.1 to 0.5 mol / L. The time of the hydrothermal reaction is 2 to 4 hours, and more preferably 3 hours.

[0012] In a preferred embodiment, in step (2), the scale and corrosion inhibitor active components are polyepoxysuccinic acid, sodium lignin sulfonate and zinc sulfate; the mass ratio of polyepoxysuccinic acid, sodium lignin sulfonate and zinc sulfate is (4.0-6.0):(0.5-0.9):(2.0-2.5), and more preferably 5:0.7:2.3.

[0013] In a preferred embodiment, in step (2), the concentration of the modified hydrotalcite-like powder in the hydrotalcite-like dispersion is 0.2-0.3 g / mL, more preferably 0.24 g / mL.

[0014] In a preferred embodiment, in step (2), the mass ratio of the modified hydrotalcite-like powder to the scale and corrosion inhibitor active component is 3:(3.5-4.5), and more preferably 3:4.

[0015] In a preferred embodiment, in step (2), the binder is one of hydroxypropyl methylcellulose, carboxymethyl cellulose and polyvinyl alcohol; and the amount of the binder is 10% to 20% of the scale and corrosion inhibitor active component.

[0016] In a preferred embodiment, in step (2), the mesh size of the sieve used for sieving is 10-100 mesh. Further preferably, the mesh size of the sieve used for sieving is at least two of 10 mesh, 25 mesh, 50 mesh, 75 mesh, and 100 mesh.

[0017] The second aspect of the present invention provides a controllable-release solid corrosion and scale inhibitor prepared by the above-mentioned preparation method.

[0018] The technical solution of the present invention has the following advantages and beneficial effects: When preparing the solid corrosion and scale inhibitor, the present invention uses three metal salts (manganese nitrate, zinc nitrate, and aluminum nitrate) as precursors and xanthan gum as a modifier to prepare a Mn-Zn-Al ternary modified hydrotalcite-like material through a hydrothermal reaction; the ternary modified hydrotalcite-like material is further mixed with a scale and corrosion inhibitor active component for granulation and sieving to prepare solid corrosion and scale inhibitors of different sizes.

[0019] In the method of the present invention, xanthan gum performs ion exchange with the lamellar structure of hydrotalcite-like substances (LDHs) during the hydrothermal reaction, thereby intercalating into the interlayers of LDHs, which is not only beneficial to improving the structural stability of hydrotalcite-like substances, but also beneficial to improving the adsorption strength of hydrotalcite-like substances on scale and corrosion inhibitory active components, achieving effective encapsulation of scale and corrosion inhibitory active components, avoiding the explosive release and sudden release of active components during use, thereby achieving the purpose of controllable regulation of the release rate of active components.

[0020] Furthermore, the present invention uses modified hydrotalcite as a loading matrix for the scale and corrosion inhibition active component, which is beneficial to the scale and corrosion inhibition effect of the active component, and is also beneficial to improving the stability and service life of the scale and corrosion inhibition active component. In particular, the present invention can select corrosion and scale inhibitors of different sizes for grading according to the actual needs of the scale inhibition environment, so as to achieve the purpose of effectively controlling the release rate and achieving a customized scale and corrosion inhibition effect.

[0021] In addition, the preparation method of the present invention has a simple process and mild conditions, and the prepared solid corrosion inhibitor and scale inhibitor can be directly used for water treatment, and the use method is simple and convenient. Moreover, the solid corrosion inhibitor and scale inhibitor prepared by the above method of the present invention has raw materials that do not contain phosphorus, is green and environmentally friendly, and does not cause environmental pollution in the natural environment. At the same time, the present invention can obtain a series of scale inhibitor products with different release rates by preparing a series of scale inhibitors of different molding sizes and proportioning scale inhibitors of different sizes according to needs. Before use, it can be controlled to be released according to predetermined descaling needs and release requirements, thereby achieving precise and controllable release of the scale inhibitor.

[0022] Therefore, the solid corrosion and scale inhibitor of the present invention can reduce the formation of scale and effectively delay the corrosion of metals, and has a long action period. It can also achieve the effect of controlled release of scale and corrosion inhibitor active components, which not only helps to improve the utilization rate of water resources and reduce the amount of water treatment additives, but also has good application prospects and development potential in the development and application of scale inhibitors for water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The cumulative release rate change results of the scale inhibitors in Example 1 of the present invention (test sample-A to test sample-C) and the scale inhibitors in the control group (control sample-A to control sample-C); Figure 2 The scale inhibition rate change results of the scale inhibitor of Example 1 of the present invention (test sample-B) and the scale inhibitors of Comparative Examples 1 to 5 (comparative sample-A to comparative sample-E) are shown. DETAILED DESCRIPTION

[0024] In order to more clearly understand the above-mentioned objects, features and advantages of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. It should be noted that, in the absence of conflict, the features in the embodiments of the present invention can be combined with each other. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from this description. Therefore, the scope of protection of the present invention is not limited by the specific embodiments disclosed below. For ordinary technicians in this field, other embodiments can also be obtained based on the provided embodiments without paying creative labor. In the embodiment of the present invention, xanthan gum comes from Shanghai Aladdin; the model of sodium lignin sulfonate is TY-8912; polyepoxysuccinic acid is a liquid preparation with a mass content of 50%. The mass concentration of ammonia water is 25%~28%. Other raw materials, unless otherwise specified, are all materials commonly used in the field that can be obtained through commercial channels.

[0025] Example 1 A controllable release solid corrosion and scale inhibitor, the preparation method of which comprises the following steps: (1) Manganese nitrate tetrahydrate (0.01 mol), zinc nitrate hexahydrate (0.01 mol), and aluminum nitrate nonahydrate (0.01 mol) were dissolved in 60 mL of deionized water, and then 3 g of xanthan gum was added. The mixture was stirred for 10 min, and ammonia water was added to adjust the pH of the system to 9. The resulting mixture was transferred to a high-pressure reactor and subjected to hydrothermal reaction at 120° C. for 3 h. After the reaction, the product was filtered and washed with deionized water until neutral. After washing, the product was vacuum dried at 80° C. for 4 h, and then ground to obtain a uniform powder, which is the modified hydrotalcite-like powder.

[0026] (2) 6 g of modified hydrotalcite-like powder was ultrasonically dispersed in 25 mL of deionized water to obtain a hydrotalcite-like dispersion; 5 g of polyepoxysuccinic acid, 0.7 g of sodium lignin sulfonate, 2.3 g of zinc sulfate and 1.5 g of a binder (polyvinyl alcohol) were mixed evenly at 40 °C to obtain an active component mixture. The hydrotalcite-like dispersion was slowly added to the active component mixture, stirred and mixed for 30 min, then granulated and dried, and passed through 10 mesh, 50 mesh, and 100 mesh sieves, respectively, to obtain spherical solid corrosion and scale inhibitors of different particle sizes (respectively recorded as test sample-A, test sample-B, and test sample-C).

[0027] Example 2 A controllable release solid corrosion and scale inhibitor, the preparation method of which comprises the following steps: (1) Manganese nitrate tetrahydrate (0.012 mol), zinc nitrate hexahydrate (0.008 mol), and aluminum nitrate nonahydrate (0.01 mol) were dissolved in 50 mL of deionized water, and then 3.5 g of xanthan gum was added and stirred for 10 min. Ammonia water was added to adjust the pH of the system to 9, and the resulting mixture was transferred to a high-pressure reactor and subjected to hydrothermal reaction at 120° C. for 3 h. After the reaction, the product was filtered and washed with deionized water until neutral. After washing, the product was vacuum dried at 80° C. for 4 h and then ground to obtain a uniform powder, which is the modified hydrotalcite-like powder.

[0028] (2) 6 g of modified hydrotalcite-like powder was ultrasonically dispersed in 25 mL of deionized water to obtain a hydrotalcite-like dispersion; 5.5 g of polyepoxysuccinic acid, 0.5 g of sodium lignin sulfonate, 2.0 g of zinc sulfate and 1.5 g of a binder (polyvinyl alcohol) were mixed evenly at 40 °C to obtain an active component mixture. The hydrotalcite-like dispersion was slowly added to the active component mixture, stirred and mixed for 30 min, then granulated and dried, and passed through 10 mesh, 50 mesh, and 100 mesh sieves to obtain spherical solid corrosion and scale inhibitors of different particle sizes.

[0029] Example 3 A controllable release solid corrosion and scale inhibitor, the preparation method of which comprises the following steps: (1) Manganese nitrate tetrahydrate (0.01 mol), zinc nitrate hexahydrate (0.012 mol), and aluminum nitrate nonahydrate (0.008 mol) were dissolved in 80 mL of deionized water, and then 4 g of xanthan gum was added and stirred for 10 min. Ammonia water was added to adjust the pH of the system to 9, and the resulting mixture was transferred to a high-pressure reactor and subjected to hydrothermal reaction at 120° C. for 3 h. After the reaction, the product was filtered and washed with deionized water until neutral. After washing, the product was vacuum dried at 80° C. for 4 h and then ground to obtain a uniform powder, which is the modified hydrotalcite-like powder.

[0030] (2) 6 g of modified hydrotalcite powder was ultrasonically dispersed in 30 mL of deionized water to obtain a hydrotalcite dispersion; 6 g of polyepoxysuccinic acid, 0.5 g of sodium lignin sulfonate, 2.5 g of zinc sulfate and 1.7 g of binder (polyvinyl alcohol) were mixed evenly at 40 °C to obtain an active component mixture. The hydrotalcite dispersion was slowly added to the active component mixture, stirred and mixed for 30 min, then granulated and dried, and passed through 10 mesh, 50 mesh, and 100 mesh sieves to obtain spherical solid corrosion and scale inhibitors of different particle sizes.

[0031] Example 4 A controllable release solid corrosion and scale inhibitor, the preparation method of which comprises the following steps: (1) Manganese nitrate tetrahydrate (0.01 mol), zinc nitrate hexahydrate (0.01 mol), and aluminum nitrate nonahydrate (0.01 mol) were dissolved in 60 mL of deionized water, and then 3 g of xanthan gum was added and stirred for 10 min. Ammonia water was added to adjust the pH of the system to 10, and the resulting mixture was transferred to a high-pressure reactor and subjected to hydrothermal reaction at 110° C. for 4 h. After the reaction, the product was filtered and washed with deionized water until neutral. After washing, the product was vacuum dried at 80° C. for 4 h, and then ground to obtain a uniform powder, which is the modified hydrotalcite-like powder.

[0032] (2) 6 g of modified hydrotalcite-like powder was ultrasonically dispersed in 25 mL of deionized water to obtain a hydrotalcite-like dispersion; 5 g of polyepoxysuccinic acid, 0.7 g of sodium lignin sulfonate, 2.3 g of zinc sulfate and 1.5 g of binder (polyvinyl alcohol) were mixed evenly at 40 °C to obtain an active component mixture. The hydrotalcite-like dispersion was slowly added to the active component mixture, stirred and mixed for 30 min, then granulated and dried, and passed through 10 mesh, 50 mesh, and 100 mesh sieves to obtain spherical solid corrosion and scale inhibitors of different particle sizes.

[0033] Example 5 A controllable release solid corrosion and scale inhibitor, the preparation method of which comprises the following steps: (1) Manganese nitrate tetrahydrate (0.01 mol), zinc nitrate hexahydrate (0.01 mol), and aluminum nitrate nonahydrate (0.01 mol) were dissolved in 60 mL of deionized water, and then 3 g of xanthan gum was added and stirred for 10 min. Ammonia water was added to adjust the pH of the system to 8.5. The resulting mixture was transferred to a high-pressure reactor and subjected to hydrothermal reaction at 130° C. for 2 h. After the reaction, the product was filtered and washed with deionized water until neutral. After washing, the product was vacuum dried at 80° C. for 4 h and then ground to obtain a uniform powder, which is the modified hydrotalcite-like powder.

[0034] (2) 6 g of modified hydrotalcite-like powder was ultrasonically dispersed in 25 mL of deionized water to obtain a hydrotalcite-like dispersion; 5 g of polyepoxysuccinic acid, 0.7 g of sodium lignin sulfonate, 2.3 g of zinc sulfate and 1.5 g of binder (polyvinyl alcohol) were mixed evenly at 40 °C to obtain an active component mixture. The hydrotalcite-like dispersion was slowly added to the active component mixture, stirred and mixed for 30 min, then granulated and dried, and passed through 10 mesh, 50 mesh, and 100 mesh sieves to obtain spherical solid corrosion and scale inhibitors of different particle sizes.

[0035] Comparative Example 1 A solid corrosion inhibitor and scale inhibitor, the preparation method of which is different from that of Example 1 in that: step (1) is omitted; step (2) is: 6 g of xanthan gum is ultrasonically dispersed in 25 mL of deionized water to obtain a xanthan gum solution; 5 g of polyepoxysuccinic acid, 0.7 g of sodium lignin sulfonate, 2.3 g of zinc sulfate and 1.5 g of a binder (polyvinyl alcohol) are mixed evenly under heating conditions at 40° C. to obtain an active component mixed solution. The xanthan gum solution is slowly added to the active component mixed solution, stirred and mixed for 30 minutes, and then granulated, dried, and passed through a 50-mesh sieve to obtain a spherical solid corrosion inhibitor and scale inhibitor (referred to as comparative sample-A).

[0036] Comparative Example 2 A solid corrosion inhibitor and scale inhibitor, the preparation method of which is different from that of Example 1 in that: in step (1), nickel nitrate hexahydrate is used instead of manganese nitrate tetrahydrate in the same molar amount; in addition, in step (2), after granulation and drying, the mixture is sieved through a 50-mesh sieve, and the amounts of the remaining raw materials and the preparation conditions are the same as those of Example 1, thereby preparing a spherical solid corrosion inhibitor and scale inhibitor (referred to as comparative sample-B).

[0037] Comparative Example 3 A solid corrosion inhibitor and scale inhibitor, the preparation method of which is different from that of Example 1 in that: in step (1), xanthan gum is not added to obtain hydrotalcite-like powder, and the hydrotalcite-like powder is used in step (2); in addition, in step (2), after granulation and drying, the powder is sieved through a 50-mesh sieve, and the amounts of other raw materials and the preparation conditions are the same as those of Example 1, to obtain a solid corrosion inhibitor and scale inhibitor (referred to as comparative sample-C).

[0038] Comparative Example 4 A solid corrosion inhibitor and scale inhibitor, the preparation method of which is different from that of Example 1 in that: in step (1), an equal amount of sodium alginate is used instead of xanthan gum to obtain a modified hydrotalcite-like powder, and the modified hydrotalcite-like powder is used in step (2); in addition, after granulation and drying in step (2), the powder is passed through a 50-mesh sieve, and the amounts of other raw materials and the preparation conditions are the same as those in Example 1, to prepare a spherical solid corrosion inhibitor and scale inhibitor (referred to as comparative sample-D).

[0039] Comparative Example 5 A solid corrosion inhibitor and scale inhibitor, the preparation method of which is different from that of Example 1 in that: in step (1), xanthan gum is not added to obtain hydrotalcite-like powder, and the hydrotalcite-like powder is used in step (2); step (2) specifically comprises: ultrasonically dispersing a mixture of 6 g of hydrotalcite-like powder and xanthan gum (the mixing mass ratio of the two is 3:1) in 25 mL of deionized water to obtain a mixed dispersion; and uniformly mixing 5 g of polyepoxysuccinic acid, 0.7 g of sodium lignin sulfonate, 2.3 g of zinc sulfate and 1.5 g of a binder (polyvinyl alcohol) under heating conditions of 40° C. to obtain an active component mixed solution. The mixed dispersion is slowly added to the active component mixed solution, stirred and mixed for 30 minutes, and then granulated, dried, and passed through a 50-mesh sieve to obtain a spherical solid corrosion inhibitor and scale inhibitor (referred to as comparative sample-E).

[0040] Test Example 1: Determination of scale inhibition effect The calcium phosphate scale inhibition performance of the scale inhibitors (all with a size of 50 mesh) prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was tested with reference to GB / T 22626-2008 "Determination of scale inhibition performance of water treatment agents - calcium phosphate precipitation method". The dosage was 5 mg / L, and the treatment conditions were: temperature of 80±1°C, time of 10 h. The test results of calcium phosphate scale inhibition efficiency are shown in Table 1.

[0041] Referring to GB / T 16632-2019 "Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method", the scale inhibition performance of the scale inhibitors (all with a size of 50 mesh) prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was tested. The dosage was 5 mg / L, and the treatment conditions were: temperature 80±1°C, time 10 h, and the test results of calcium carbonate scale inhibition efficiency are shown in Table 1.

[0042] Table 1. Scale inhibition effect of different scale inhibitors on calcium phosphate and calcium carbonate

[0043] From the results in Table 1, it can be seen that the scale inhibition rates of the scale inhibitors of Examples 1 to 5 of the present invention for calcium phosphate and calcium carbonate are all above 90%, which is better than the scale inhibitors provided in Comparative Examples 1 to 5, and the scale inhibition effect for calcium carbonate is the best.

[0044] Test Example 2: Determination of release rate and stability in use In this test, the solid corrosion and scale inhibitors (test sample-A, test sample-B, test sample-C) with different particle sizes prepared in Example 1 of the present invention were compared with the scale inhibitor samples prepared by the conventional method. Furthermore, the solid corrosion and scale inhibitor (test sample-B) prepared in Example 1 of the present invention was compared with the solid corrosion and scale inhibitors (comparative sample-A to comparative sample-E) prepared in comparative examples 1 to 5 for stability in use.

[0045] Among them, when comparing the release rates, the scale inhibitor sample prepared by the conventional method was used as the control sample. The specific preparation process was: 5g of polyepoxysuccinic acid, 0.7g of sodium lignin sulfonate, 2.3g of zinc sulfate and 1.5g of binder (polyvinyl alcohol) were mixed evenly under heating conditions at 40°C, and then granulated and dried, and passed through 10-mesh, 50-mesh and 100-mesh sieves respectively to obtain spherical solid corrosion and scale inhibitors of different particle sizes (respectively recorded as control sample-A, control sample-B, and control sample-C).

[0046] The release rate and stability under static conditions were determined as follows: 1g of antiscalant sample was weighed and packed in different gauze bags, and then placed in a 1L simulated water environment (containing 300mg / L Ca 2+ , 200mg / L HCO¯), the temperature was kept at 60±1℃ for static scale inhibition test, each scale inhibitor was slowly released into the water body, 20mL of supernatant was taken after 1 day, and the concentration and scale inhibition rate of the scale inhibitor were determined. After sampling, the gauze bag was taken out and put back into the newly configured 1000mL simulated water environment, and the scale inhibition test was carried out in this way. Sampling was carried out on the 1st, 5th, 10th, 20th, 30th, 40th, 50th and 60th days, and the concentration and scale inhibition rate of the scale inhibitor were determined. The cumulative release rate of the scale inhibitor and the scale inhibition rate change curve were plotted. The results are as follows: Figure 1 and Figure 2 shown.

[0047] like Figure 1 As shown in the cumulative release rate test results, the scale inhibitors of different sizes provided by the control group have a fast release rate at a test temperature of 60°C, and the rate is uncontrollable, and there is no controlled release effect. However, for the solid corrosion inhibitor and scale inhibitor provided in Example 1 of the present invention, the release rate of large-sized scale inhibitors is slow, and the release rate of small-sized scale inhibitors is significantly accelerated. There is an obvious gradient relationship in the release amount of the effective ingredients of scale inhibitors of different sizes, and it has an excellent controllable release effect, so it can timely adjust the release rate of corrosion and scale inhibitor components according to the application scenario. In addition, the scale inhibitor of Example 1 has a slower release rate of the effective ingredients than the control group, is less prone to sudden release and burst release, and is also conducive to extending the effective scale inhibition days.

[0048] like Figure 2As shown in the scale inhibition rate test results, at the same dosage and the same size, the scale inhibition effect of each group of scale inhibitors decreased to varying degrees as time went on. Among them, the scale inhibitor provided in Example 1 of the present invention has the highest scale inhibition efficiency, and its scale inhibition efficiency still reaches 71.3% after a 60-day test period. The scale inhibition efficiencies of the scale inhibitors provided in Comparative Examples 1 to 5 are 32.9%, 64.4%, 49.3%, 54.3%, and 60.8% respectively after 60 days. Therefore, the scale inhibitor of the present invention can achieve a better scale inhibition effect, and has good stability in use, and a long effective scale inhibition time and service life.

[0049] Test Example 3: Determination of Corrosion Inhibition Effect The corrosion inhibition performance of the scale inhibitors (all with a size of 50 mesh) prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was tested with reference to GB / T 18175-2014 "Determination of corrosion inhibition performance of water treatment agents - Rotating hanging plate method". The test piece used in the test was a brass test piece, the dosage of the scale inhibitor was 50 mg / L, the temperature was 50±1°C, the treatment time was 96h, and the test results of the brass corrosion rate and corrosion inhibition rate are shown in Table 2.

[0050] Table 2. Comparison of corrosion inhibition effects of different scale inhibitors

[0051] From the comparison of the corrosion inhibition effects of the scale inhibitors of Examples 1 to 5 and Comparative Examples 1 to 5 in Table 2, it can be seen that the corrosion rate and corrosion inhibition rate of the scale inhibitor provided by the embodiments of the present invention are better than those of the comparative examples, indicating that the scale inhibitor of the present invention has good corrosion inhibition performance, is more conducive to reducing metal corrosion, and prolongs the service life of the pipeline.

[0052] Based on the above test results, it can be seen that the solid corrosion and scale inhibitor of the present invention can reduce the formation of scale and effectively delay the corrosion of metals, and has a long action period. In particular, it can achieve the effect of controlled release of scale and corrosion inhibitor active components, which not only helps to improve the utilization rate of water resources and reduce the amount of water treatment additives, but also has good application prospects and development potential in the development and application of scale inhibitors for water treatment.

[0053] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a controlled-release solid corrosion and scale inhibitor, characterized in that: The following steps are involved: (1) Mixing manganese nitrate, zinc nitrate, aluminum nitrate and xanthan gum in water, and then adjusting the pH of the system to 8-10 to obtain a mixed solution; transferring the mixed solution to a high-pressure reactor, and performing a hydrothermal reaction at a temperature of 110-130° C.; filtering the product after the reaction, and then washing, drying and grinding to obtain a modified hydrotalcite-like powder; (2) Dispersing the modified hydrotalcite-like powder in water to obtain a hydrotalcite-like dispersion; mixing the scale and corrosion inhibitor active component with a binder to obtain an active component mixed solution; adding the hydrotalcite-like dispersion to the active component mixed solution, mixing, and then granulating, drying, and sieving to obtain solid corrosion and scale inhibitors of different sizes with controlled release.

2. The method for preparing a controlled-release solid corrosion and scale inhibitor according to claim 1, characterized in that: In step (1), the manganese nitrate is manganese nitrate tetrahydrate; the zinc nitrate is zinc nitrate hexahydrate; and the aluminum nitrate is aluminum nitrate nonahydrate.

3. The method for preparing a controlled-release solid corrosion and scale inhibitor according to claim 1, characterized in that: In step (1), the molar ratio of manganese nitrate, zinc nitrate and aluminum nitrate is 1:(0.8-1.2):(0.8-1.2); the dosage ratio of manganese nitrate, xanthan gum and water is 0.01 mol:(2-4) g:(50-80) mL.

4. The method for preparing a controlled-release solid corrosion and scale inhibitor according to claim 1, characterized in that: In step (1), the pH of the system is adjusted using aqueous ammonia or sodium hydroxide solution; and the hydrothermal reaction time is 2 to 4 hours.

5. The method for preparing a controlled-release solid corrosion and scale inhibitor according to any one of claims 1 to 4, characterized in that: In step (2), the scale and corrosion inhibitor active components are polyepoxysuccinic acid, sodium lignin sulfonate and zinc sulfate; the mass ratio of polyepoxysuccinic acid, sodium lignin sulfonate and zinc sulfate is (4.0-6.0): (0.5-0.9): (2.0-2.5).

6. The method for preparing a controlled-release solid corrosion and scale inhibitor according to any one of claims 1 to 4, characterized in that: In step (2), the concentration of the modified hydrotalcite-like powder in the hydrotalcite-like dispersion is 0.2-0.3 g / mL.

7. The method for preparing a controlled-release solid corrosion and scale inhibitor according to any one of claims 1 to 4, characterized in that: In step (2), the mass ratio of the modified hydrotalcite-like powder to the scale and corrosion inhibitor active component is 3: (3.5-4.5).

8. The method for preparing a controlled-release solid corrosion and scale inhibitor according to any one of claims 1 to 4, characterized in that: In step (2), the binder is one of hydroxypropyl methylcellulose, carboxymethyl cellulose and polyvinyl alcohol; the amount of the binder is 10% to 20% of the scale and corrosion inhibition active component.

9. The method for preparing a controlled-release solid corrosion and scale inhibitor according to any one of claims 1 to 4, characterized in that: In step (2), the mesh size of the sieve used for sieving is 10-100 mesh.

10. A controlled-release solid corrosion and scale inhibitor prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Non-phosphorous corrosion and scale inhibitor containing lignosulfonate and application thereof

    CN103420497A

  • Scale and corrosion inhibitor

    CN107325802A

  • Preparation method of corrosion inhibitor composite anion intercalated hydrotalcite

    CN111348666A

  • Modified hydrotalcite and paint remover containing same

    CN119320575A

  • Scale inhibition and dispersion agent for treating industrial circulating water and preparation method of scale inhibition and dispersion agent

    CN119569969A

Cited By

  • Corrosion and scale inhibition proppant and preparation method thereof

    CN120555045A